Australian teacher stress, well‐being, self‐efficacy, and safety during the COVID‐19 pandemic - Billett, Paulina; Turner, Kristina; Li, Xia (Psychology in the schools, 2023)
The 2020 COVID pandemic radically altered the way in which individuals live and work. For teachers, this entailed a shift in their teaching practice, with large numbers of schools around Australia and the world closing for prolonged periods of time and moving to an “online” format. This required teachers to quickly adapt their teaching practices adding further stress to an already stressful environment. In this article, we examine the relationships between teachers' stress, teachers' self‐efficacy, and teachers' well‐being during the COVID pandemic. The study presents the results from a quantitative survey undertaken in June and July 2020 with 534 teachers around Australia. While the study found that, overall, most teachers (77.29%) reported that they were not feeling anxious in their teaching role, teachers' responses indicated that they were experiencing high levels of stress and low levels of positive feelings such as joy, positivity, and contentment in their work during the COVID‐19 pandemic negatively impacting their well‐being and self‐efficacy. ePractitioner points The COVID pandemic negatively impacted teachers' well‐being and self‐efficacy. Many teachers reported feeling lonely and isolated during the pandemic. Teachers' responses indicated that they were experiencing high levels of stress during the COVID‐19 pandemic. This was largely perceived by respondents to be the result of increased pressures in workload, due to the shift to online learning. Teachers' responses indicated that they were feeling unsafe during the COVID‐19 pandemic and this was positively correlated to stress scores.